Revisiting the Hot Hand theory with free throw data in a multivariate framework - Arkes, J. (Journal of Quantitative Analysis in Sports, 2010)
Despite the conventional wisdom of the existence of the "hot hand" in basketball, studies have found no or weak evidence for the hot hand in game situations, although stronger evidence in controlled settings. Almost all studies have tested for the hot hand in univariate frameworks, often with inadequate power. I use a sample based on all free throws during the 2005-06 NBA season. With a multivariate framework with individual fixed effects, I find evidence for the "hot hand" in that making the first free throw is associated with a significantly higher probability of making the second free throw.